Comprehensive investigation of rooftop photovoltaic power plants with monocrystalline polycrystalline and thin-film technologies for exergy economic and environmental assessments - Abdelhak Lekbir; Samir Hassani; Putri Nor Liyana Mohamad Radzi; Saad Mekhilef; Kok Soon Tey; Abdullahi Mohamed Samatar; Obaid Alshammari (Scientific Reports)
Abstract This research aims to conduct an exergy, economic, and environmental analysis of a 6.57 kWp rooftop photovoltaic (PV) power plant that combines different PV technologies, comprising 2 kWp of poly-crystalline (p-Si), 1.87 kWp of mono-crystalline (m-Si), and 2.7 kWp of thin-film amorphous silicon (a-Si) technologies. A comprehensive assessment was conducted to evaluate the environmental and techno-economic parameters of a PV plant system. This study is based on the performance data obtained over four years of energy production under the weather conditions of Kuala Lumpur, Malaysia. The embodied energy required for the manufacturing of the PV power plant was estimated using embodied energy indices available in the literature. Additionally, a detailed economic evaluation was conducted based on the electricity costs in Malaysia. Moreover, the environmental impact was assessed over the plant’s life cycle, considering the emission factors of coal power plants. Results indicate that the exergy payback time for the different technologies i.e., m-Si, p-Si, a-Si, when operated individually, and when combined within a single PV system, are found to be ~ $$10, 4.2, 2.4$$ , and $$6.3$$ years, respectively. Over its life cycle, it was found that the PV plant emits about $${39.3\text{ tCO}}_{2}$$ . Emission breakdown analysis has revealed that the manufacturing process of the m-Si, p-Si, a-Si, and the monitoring systems contribute to $$32.4{%}$$ , $$22.4{%}$$ , $$17.3{%}$$ , and $$27.8{%}$$ of $${\text{CO}}_{2}$$ emissions, respectively. However, the PV power plant could offset about $$6.2\text{ t}{\text{CO}}_{2}$$ annually, equivalent to the emission of a car over approximately 3 years. This study offers critical insights into the exergy efficiency, environmental impact, and economic viability of a grid-connected rooftop PV power plant that integrates multiple PV technologies under tropical climate conditions.